A Clinical Predictive Model of Central Lymph Node Metastases in Papillary Thyroid Carcinoma - Wang, Zipeng; Chang, Qungang; Zhang, Hanyin; Du, Gongbo; Li, Shuo; Liu, Yihao; Sun, Hanlin; Yin, Detao (Frontiers in Endocrinology, 2022)
Background: Thyroid carcinoma is one of the most common endocrine tumors, and papillary thyroid carcinoma (PTC) is the most common pathological type. Current studies have reported that PTC has a strong propensity for central lymph node metastases (CLNM). Whether to prophylactically dissect the central lymph nodes in PTC remains controversial. This study aimed to explore the risk factors and develop a predictive model of CLNM in PTC. Methods: A total of 2554 patients were enrolled in this study. The basic information, laboratory examination, characteristics of cervical ultrasound, genetic test, and pathological diagnosis were collected. The collected data were analyzed by univariate logistic analysis and multivariate logistic analysis. The risk factors were evaluated and the predictive model was constructed of CLNM. Results: The multivariate logistic analysis showed that Age (p<0.001), Gender (p<0.001), Multifocality (p<0.001), BRAF (p=0.027), Tumor size (p<0.001) were associated with CLNM. The receiver operating characteristic curve (ROC curve) showed high efficiency with an area under the ROC (AUC) of 0.781 in the training group. The calibration curve and the calibration of the model were evaluated. The decision curve analysis (DCA) for the nomogram showed that the nomogram can provide benefits in this study. Conclusion: The predictive model of CLNM constructed and visualized based on the evaluated risk factors was confirmed to be a practical and convenient tool for clinicians to predict the CLNM in PTC.